SILENT SPELLS OF HISTORY OR SHRINES AS SPIRITUAL AND CULTURAL HERITAGE (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, it is stated that pilgrimage rituals and the emergence of these rituals reflect the socio-economic life of the local population during historical periods, pilgrimage rituals also change based on the people's consciousness and worldview, and some traditions have been transformed.